Cyberthreats : the emerging fault lines of the nation state - Brenner, Susan W., 1947- (New York ; Oxford : Oxford University Press, 2009)
Susan Brenner gives a thorough explanation of how military and law enforcement personnel respond to terrorist cyberspace attacks and why bringing cyberterrorists to justice can be difficult and sometimes impossible.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Computer networks -- Law and legislation -- Criminal provisions; Political crimes and offenses; War (International law); Transnational crime